Analisis Strategi Pengembangan Kemasan Produk terhadap Volume Penjualan. Studi Kasus pada PT. Australian Indonesia Milk - Hasibuan, David H.M.; Zuhdi, Saefudin (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2005)
The purpose of the research is to find out the Strategy of product packing development implemented by the company at present. PT Indomilk obviously is able to compete with other companies although they still need to improve the packaging, because the position of the competitor is above PT Indomilk. PT Indomilk is in the position of stabile development so that it can survive and is developing the strategy product packing to increase sales volume. To determine the strategy they use correlation analysis to analyze how far the relation between packing development and the rate of sales volume. Key words: Packaging Development; Sales Volume